Parental Education and Genetics of BMI from Infancy to Old Age: A Pooled Analysis of 29 Twin Cohorts. Issue 5 (5th April 2019) - Silventoinen, Karri; Jelenkovic, Aline; Latvala, Antti; Yokoyama, Yoshie; Sund, Reijo; Sugawara, Masumi; Tanaka, Mami; Matsumoto, Satoko; Aaltonen, Sari; Piirtola, Maarit; Freitas, Duarte L.; Maia, José A.; et al.
Abstract : Objective: The objective of this study was to analyze how parental education modifies the genetic and environmental variances of BMI from infancy to old age in three geographic‐cultural regions. Methods: A pooled sample of 29 cohorts including 143, 499 twin individuals with information on parental education and BMI from age 1 to 79 years (299, 201 BMI measures) was analyzed by genetic twin modeling. Results: Until 4 years of age, parental education was not consistently associated with BMI. Thereafter, higher parental education level was associated with lower BMI in males and females. Total and additive genetic variances of BMI were smaller in the offspring of highly educated parents than in those whose parents had low education levels. Especially in North American and Australian children, environmental factors shared by co‐twins also contributed to the higher BMI variation in the low education level category. In Europe and East Asia, the associations of parental education with mean BMI and BMI variance were weaker than in North America and Australia. Conclusions: Lower parental education level is associated with higher mean BMI and larger genetic variance of BMI after early childhood, especially in the obesogenic macro‐environment. The interplay among genetic predisposition, childhood social environment, and macro‐social context is important for socioeconomic differences in BMI.